LIONÇO, Tatiana; DINIZ, Débora (Orgs.). Homofobia & educação: um desafio ao silêncio - Silveira, Viviane Teixeira; Rial, Carmen (Revista Estudos Feministas, 2010)
LIONÇO, Tatiana; DINIZ, Débora (Orgs.). Homofobia & educação: um desafio ao silêncio